Gastric Electrical Stimulation with the Enterra System: A Systematic Review - Nikhil Lal; Sam Livemore; Declan Dunne; Iftikhar Khan (Gastroenterology Research and Practice)
Background. Gastric electrical stimulation (GES) is a surgically implanted treatment option for refractory gastroparesis. Aim. To systematically appraise the current evidence for the use of gastric electrical stimulation and suggest a method of standardisation of assessment and follow-up in these patients. Methods. A systematic review of PubMed, Web of Science, DISCOVER, and Cochrane Library was conducted using the keywords including gastric electrical stimulation, gastroparesis, nausea, and vomiting and neuromodulation, stomach, central nervous system, gastric pacing, electrical stimulation, and gastrointestinal. Results. 1139 potentially relevant articles were identified, of which 21 met the inclusion criteria and were included. The quality of studies was variable. There was a variation in outcome measures and follow-up methodology. Included studies suggested significant reductions in symptom severity reporting over the study period, but improvements in gastric emptying time were variable and rarely correlated with symptom improvement. Conclusion. The evidence in support of gastric electrical stimulation is limited and heterogeneous in quality. While current evidence has shown a degree of efficacy in these patients, high-quality, large clinical trials are needed to establish the efficacy of this therapy and to identify the patients for whom this therapy is inappropriate. A consensus view on essential preoperative assessment and postoperative measurement is needed.